Integrasi Tafsir Al-Qur’an dan Sains Hidrologi dalam Analisis Fenomena Hujan: Pendekatan Interdisipliner - Achmad Mughni Khoiruddin; Ilma Nailatul Izza; Andressa Muthi’ Latansa; Aniqotul Muthi'ah; Faisal Diaulhaq; Nilna Khurina Syalsabila (Ta’wiluna: Jurnal Ilmu Al-Qur'an, Tafsir dan Pemikiran Islam, 2026)
Rain is one of the kauniyah signs that represents the relationship between revelation, cosmic order, and the sustainability of life. This study aims to analyze the concept of rain in the Qur’an through a thematic (maudhu‘i) exegesis approach while formulating an integrative model between Qur’anic interpretation and science in understanding hydrological phenomena. This research employs a qualitative-descriptive method based on library research by examining Qur’anic verses related to rain, water, wind, and clouds, particularly QS. al-Anbiyā’:30, QS. al-Mu’minūn:18, and QS. ar-Rūm:48, through classical and contemporary exegesis as well as modern hydrological literature. The findings reveal that the Qur’an not only views rain as divine mercy but also contains principles of order, balance, and ecological cycles that conceptually correspond to the scientific mechanisms of evaporation, condensation, and precipitation. The novelty of this study lies in the formulation of an integrative tafsir-hydrology model based on three epistemic dimensions: the theological dimension (rain as divine mercy), the cosmological dimension (rain as a natural causal system), and the ecological dimension (rain as a foundation for environmental conservation ethics). This model goes beyond previous descriptive-integrative approaches that mainly emphasize the compatibility between Qur’anic verses and scientific facts. Therefore, this study contributes to strengthening the epistemological dialogue between revelation and science while offering a new conceptual framework for the development of scientific exegesis and Islamic environmental ethics.